UPA‐PAI‐1 heteromerization promotes breast cancer progression by attracting tumorigenic neutrophils. Issue 6 (16th May 2021) - Uhl, Bernd; A Mittmann, Laura; Dominik, Julian; Hennel, Roman; Smiljanov, Bojan; Haring, Florian; B Schaubächer, Johanna; Braun, Constanze; Padovan, Lena; Pick, Robert; Canis, Martin; Schulz, Christian; et al.
Abstract: High intratumoral levels of urokinase‐type plasminogen activator (uPA)‐plasminogen activator inhibitor‐1 (PAI‐1) heteromers predict impaired survival and treatment response in early breast cancer. The pathogenetic role of this protein complex remains obscure. Here, we demonstrate that heteromerization of uPA and PAI‐1 multiplies the potential of the single proteins to attract pro‐tumorigenic neutrophils. To this end, tumor‐released uPA‐PAI‐1 utilizes very low‐density lipoprotein receptor and mitogen‐activated protein kinases to initiate a pro‐inflammatory program in perivascular macrophages. This enforces neutrophil trafficking to cancerous lesions and skews these immune cells toward a pro‐tumorigenic phenotype, thus supporting tumor growth and metastasis. Blockade of uPA‐PAI‐1 heteromerization by a novel small‐molecule inhibitor interfered with these events and effectively prevented tumor progression. Our findings identify a therapeutically targetable, hitherto unknown interplay between hemostasis and innate immunity that drives breast cancer progression. As a personalized immunotherapeutic strategy, blockade of uPA‐PAI‐1 heteromerization might be particularly beneficial for patients with highly aggressive uPA‐PAI‐1 high tumors. Synopsis: Uhl et al report that heteromerization of the serine protease urokinase‐type plasminogen activator (uPA) and the serpin plasminogen activator inhibitor‐1 (PAI‐1) enforces the trafficking of pro‐tumorigenic neutrophils to malignant lesions in highly aggressive subtypes of breast cancer. High levels of uPA‐PAI‐1 heteromers in human breast cancer were related to extensive neutrophil infiltration of the malignant tumors and a poor clinical outcome. uPA‐PAI‐1 heteromers induced the release of the cytokine TNF in perivascular macrophages via VLDLr, in turn activating microvascular endothelial cells. Endothelially‐deposited uPA‐PAI‐1 heteromers subsequently supported intravascular adhesion and extravasation of circulating neutrophils by promoting β2 integrin clustering on their cell surface. uPA‐PAI‐1‐primed neutrophils unfolded pro‐tumorigenic properties, potently stimulating breast cancer cell proliferation by the release of neutrophil elastase. Pharmacological blockade of uPA‐PAI‐1 heteromerization by a novel small molecule inhibitor prevented neutrophil infiltration and tumor progression in experimental breast cancer. Abstract : Uhl et al report that heteromerization of the serine protease urokinase‐type plasminogen activator (uPA) and the serpin plasminogen activator inhibitor‐1 (PAI‐1) enforces the trafficking of pro‐tumorigenic neutrophils to malignant lesions in highly aggressive subtypes of breast cancer.